Relevance and prospective study of the chemical professional in the national, regional and current world scenario - Almachi–Villalba, Dennys Paul (2024)
This research aimed to highlight the importance of chemical professionals at national, regional and global levels; for this, a systematic review was conducted to demonstrate the capabilities of chemical professionals who are closely linked to regulations set by the Ecuadorian Institute of Standardization (INEN), Codex Alimentarius, among others that govern the operations of companies to research and develop products of various economic sectors with quality. Regarding the linkage of chemical professionals in a global context, the literature review made it possible to align the profile of the chemical professional with the Sustainable Development Goals (SDGs), providing the basis for curriculum design or professional training content. On the other hand, surveys were conducted to representatives of companies in the industrial sector related to chemistry to consult cleaner production activities in the framework of the SDGs, where waste recycling stood out with 30.43%. To deepen the responses, focus groups were conducted, where company representatives expressed a clear interest in closer ties with academic institutions to access updated knowledge, continuous training and advice. In addition, they highlighted the need for chemical professionals to possess leadership, teamwork and effective communication skills. These findings show the need to strengthen collaboration between industry and academia to improve the implementation of sustainable practices in companies where chemical professionals have a relevant role in solving environmental challenges and promoting sustainable practices in various economic sectors.